Percepción de adquisición de competencias genéricas en estudiantes de Psicología que inician y finalizan su formación - Suárez Cretton, Ximena Alejandra (Universidad de Costa Rica, 2017)
The aim of the study was to verify the level of acquisition of generic skills that psychology students receive in their training process. Comparing two groups of students, one who began his career and one that ends achieve this. The total sample consisted of 217 students of the Psychology course, from five universities. Data collection was conducted through the application of Generic Skills Questionnaire Tuning Latino Americano (2007) in two measurement modes: level of importance and level of achievement. The statistical comparison is made in dimensions or groups of powers, and individually through Anova test. The skills most increased ar. The results indicate that students perceive only a slight increase in skills in the comparison between the group starts versus the ends, for older students. The most increased competences are Capacity for abstraction, analysis and synthesis; ability to apply knowledge in practice skills to search, process and analyze information; ability to formulate and manage projects. Exhibit dissatisfaction with self-perceived competence level. The actions taken by universities partially contribute to the development of generic skills necessary to becoming an assessment and analysis of the implementation process used by universities to convert their content skills programs